PARAMETRIC, NONLINEAR KINETIC AND THERMODYNAMIC MODELING OF PETROLEUM ETHER-BASED NEEM SEED OIL EXTRACTION PROCESS - Sunday. U. John; Philomena Igbokwe K.; Joseph Nwabanne T.; Onu C. E.; Nweke C. N.; Ajali J. J.; Ejiofor C. C.; Nwokedi I. C. (International Journal of Innovations in Engineering Research and Technology, 2023)
The parametric, thermodynamic, and nonlinear kinetic modeling and the impacts of process factors on the Neem oil extraction process were studied using petroleum ether as solvent. Power law, pseudo-second-order, parabolic-diffusion, pseudo-first-order, Elovich, and hyperbolic models were the kinetic models examined. Process parameters such as average particle size, time, and temperature of the oil extraction were studied. The parameters of thermodynamics, including enthalpy, entropy, and Gibb free energy, were determined. It was discovered that while the yield of oil extraction varied inversely with an increase in particle size, it varied directly with increases in temperature and time. At 74 oC, 0.1 mm, and 180 minutes throughout the extraction process, the highest oil yield of 38.8% was achieved. In terms of performance, the hyperbolic, parabolic, elovich, and power-law models gave an excellent fitting to the experimental data. The models that best fitted the experimental kinetics data under investigation were the power-law and parabolic models, which concurrently had the lowest average SSE and RMSE values, and the highest R2 and adj- R2. Pseudo-first- and pseudo-second-order models, however, failed to provide a sufficient fit for the experimental data. The endothermic, irreversible, and spontaneous nature of the Neem oil extraction process was shown by the average Gibb free energy, enthalpy, and entropy values of the process at 328K and 0.1mm, which were -1.54kJ/mol, 30.13kJ/mol, and 0.10kJ/mol, respectively.